2018
DOI: 10.1093/jas/sky432
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofBacillus amyloliquefaciensandBacillus subtilison ileal digestibility of AA and total tract digestibility of CP and gross energy in diets fed to growing pigs1

Abstract: The objective of this experiment was to test the hypothesis that the apparent ileal digestibility (AID) of AA, CP, and GE, the apparent total tract digestibility (ATTD) of CP and GE, and the apparent hindgut digestibility of CP and GE by growing pigs may be improved by supplementing diets with two direct-fed microbials (DFM) containing different Bacillus strains. Twenty-four growing barrows (initial BW: 22.69 ± 1.48 kg) that had a T-cannula installed in the distal ileum were individually housed and randomly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 35 publications
2
25
2
Order By: Relevance
“…Thus, the results of the present study support the hypothesis that the probiotic effect of Bacillus strains tested in the present trial can be ascribed to an improvement of feed digestibility by their enzymatic activity [56, 57]. This has also been confirmed by in vitro data showing secretion of NSP-enzymes and proteases by DSM25840 and DSM25841 [8] and by in vivo studies showing improved protein digestibility when these two strains were fed to grower-finisher pigs [58]. Despite an improvement of growth performance in probiotic groups was therefore expected in the present study, this result may be lack because only the most performing pigs were kept in the CO group.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the results of the present study support the hypothesis that the probiotic effect of Bacillus strains tested in the present trial can be ascribed to an improvement of feed digestibility by their enzymatic activity [56, 57]. This has also been confirmed by in vitro data showing secretion of NSP-enzymes and proteases by DSM25840 and DSM25841 [8] and by in vivo studies showing improved protein digestibility when these two strains were fed to grower-finisher pigs [58]. Despite an improvement of growth performance in probiotic groups was therefore expected in the present study, this result may be lack because only the most performing pigs were kept in the CO group.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the use of Bacillus as feed additives rather than antibiotics is justified in current research. An increasing number of Bacillus strains have been developed for use as animal feed additives [3,4].…”
Section: Introductionmentioning
confidence: 99%
“… Farhat-Khemakhem et al (2018) reported that BA could ferment and hydrolyse complex carbohydrates and oligosaccharides, some being anti-nutrients such as non-starch polysaccharides, which leads to improved digestibility of feed components. Furthermore, the positive effects of BA supplementation on nutrient digestibility have also been previously observed in pigs and mice ( Blavi et al., 2019 ; Geeraerts et al., 2015 ). Positive alteration in gut microbiota, followed by improved digestibility of nutrients may be the underlying reason for the improved meat yield in this study.…”
Section: Discussionmentioning
confidence: 58%